Association of thrombocytopenia with preeclampsia in a sample of women during labor - M. Salih, Dlvin Sartip; Alalaf, Shahla Karim (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Thrombocytopenia (platelet count < 150 × 109/L) is considered the second leading responsible factor in blood disorders in pregnancy after anemia. Substantial thrombocytopenia has been shown to associate with medical conditions. The present study aimed to compare the levels of platelets during labor between the patients diagnosed with preeclampsia and their age-matched healthy subjects. Methods: In this case-control study, the thrombocytopenia was compared between 55 patients diagnosed with preeclampsia and 59 age-matched healthy controls. In this study, the thrombocytopenia was categorized as follows; normal (150-400 × 109/L), mild (100-149 × 109/L), moderate (50-99 × 109/L), and severe (<50 ×109/L). Results: The study showed that the cases and controls were comparable in general information. The number of platelets was significantly lower in patients with preeclampsia (73.58 ± 26.05) compared to the controls (262.05 ± 81.01; and the P <0.0001). The serum bilirubin (P <0.0001) and the serum creatinine (P = 0.002) were substantially lower in the cases compared to the controls in contrast with urine protein (P <0.0001). The patients with preeclampsia were more likely to undergo an emergency cesarean section (65.5% vs. 11.9%), to have antepartum hemorrhage complications (67.3% vs. 18.6%), to get any kind of hypertensive disorders in pregnancy, and to admit the newborns to neonatal intensive care unit (60.0% vs. 35.6%). Conclusion: The present study showed that the preeclamptic patients had lower platelet count compared to non-pre-eclamptic. In addition, they were more likely to have more obstetrical complications.